(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Modern transport projects are complex, multi-stage and long-term, associated with significant calculations, changing schedules, matching resources, analyzing different scenarios for their impact on the development of transport systems and infrastructure. These projects are implemented in a dynamic external environment with a great influence of rapidly changing political, social and natural factors. This objectively requires the application of flexibility in the planning and determination of the various options for development and the search for new approaches to managing transport projects and ensuring the necessary dynamics. Through the application of artificial intelligence, the flexibility in planning and implementation of these transport projects can be improved. This article examines the possibility of using artificial intelligence in transport project management. More specifically, the methodological essence is emphasized from the point of view of using artificial intelligence in the design and implementation of these projects.